The Relationship Of Knowledge Of Pre-Operative Information With The Anxiety Of Operating Patients At Ùmum Setio Husodo Hospital In 2023 - Idris, Syamsul (Jurnal EduHealth, 2023)
Surgery is a form of therapy that can pose a threat to the integrity of a person's body and soul. The planned operation can cause physiological and psychological responses in the patient. The psychological response that usually occurs in preoperative patients is anxiety. In 2023, 784 people will undergo surgery at Setio Husodo Hospital, and in January 2023, 81 people, 40% (32 people will experience anxiety. This research aims to determine the relationship between patient knowledge regarding pre-operative information and the anxiety of surgical patients at General Setio Hospital. Husodo Range in 2023. The type of research used is descriptive correlation with a cross sectional design. The population in the study was all 45 pre-operative patients. The sampling technique was purposive sampling with a total sample of 30 respondents. Data were collected through questionnaires, data were analyzed univariately with frequency distribution and bivariate correlation using the chi-square correlation test The results of the research showed that the majority of respondents had poor knowledge, namely 12 respondents (40.0%), anxiety was at a severe level for 11 respondents (36.6%). The results of the Spearman rank correlation test showed that ρ = 0.002, meaning ρ < 0.05, which means there is a relationship between knowledge and anxiety in pre-operative patients. There is a significant relationship between patient knowledge about pre-operative information and anxiety in pre-operative patients at General Setio Hospital. Husodo Range in 2023. From this research, it was found that there is a relationship between patient knowledge about pre-operative information and the anxiety of surgical patients at Setio Husodo Kisaran General Hospital. In 2023, it is recommended that nurses always increase their knowledge, especially about patient surgical information.